A multisectoral institutional arrangements approach to integrating civil registration, vital statistics, and identity management systems - Samuel Mills; Jane Kim Lee; Bahie Mary Rassekh (BMC, 2019)
Abstract This paper reviews the essential components of a recommended institutional arrangements framework of integrated civil registration and vital statistics (CRVS) and civil identification systems. CRVS typically involves several ministries and institutions, including health institutions that notify the occurrence of births and deaths; the judicial system that records the occurrence of marriages, divorces, and adoptions; the national statistics office that produces vital statistics reports; and the civil registry, to name a few. Considering the many stakeholders and close collaborations involved, it is important to establish clear institutional arrangements-"the policies, practices and systems that allow for effective functioning of an organization or group" (United Nations Development Programme, Capacity development: a UNDP primer. New York: United Nations Development Programme, 2009). An example of a component of institutional arrangements is the establishment of a multisectoral national CRVS coordination committee consisting of representatives from key stakeholder groups that can facilitate participatory decision-making and continuous communication. Another important component of institutional arrangements is to create a linkage between CRVS and the national identity management system using unique identification numbers, enabling continuously updated vital events data to be accessible to the civil identification agency. By using birth registration in the civil registry to trigger the generation of a new identification and death registration to close it, this link accounts for the flow of people into and out of the identification management system. Expanding this data link to enable interoperability between different databases belonging to various ministries and agencies can enhance the efficiency of public and private services, save resources, and improve the quality of national statistics which are useful for monitoring the national development goals and the Sustainable Development Goals. Examples from countries that have successfully implemented the recommended components of an integrated CRVS and national identity management system are presented in the paper.